2013
DOI: 10.11607/jomi.3244
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Keratinized Mucosa Width on Peri-implant Health: A Systematic Review

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
133
1
8

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(161 citation statements)
references
References 55 publications
11
133
1
8
Order By: Relevance
“…But still, there is a lack of evidence whether KM has an impact on periimplant tissue health and periimplant bone level, respectively [27,29]. The main reason for this limitation is the heterogeneity in study designs and data extraction; consecutively, there is a lack of a synoptic statistical analysis [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But still, there is a lack of evidence whether KM has an impact on periimplant tissue health and periimplant bone level, respectively [27,29]. The main reason for this limitation is the heterogeneity in study designs and data extraction; consecutively, there is a lack of a synoptic statistical analysis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies with moderate examination periods up to 5 years reported that higher plaque accumulation and gingival inflammation were associated with the absence of KM [25,26]. This statement is supported by several systematic reviews [27-29]. Dental implants with less than 2 mm of KM seem to be more prone to recession and alveolar bone loss, measured between the crestal bone level and a reference point on the implant surface [26,30].…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have reported increased gingival and plaque index scores, mucosal recession, and marginal bone resorption in areas around implants with less than 2 mm of keratinized tissue [4, 8, 1316]. Conversely, some authors have claimed that, with adequate plaque control, peri-implant tissues can be maintained in a healthy state with a minimum amount of keratinized tissue [69].…”
Section: Introductionmentioning
confidence: 99%
“…Ausencia de encía queratinizada: La deficiencia de mucosa queratinizada alrededor de los implantes, parece estar relacionada a parámetros clínicos de inflamación y a la acumulación de biolfim. Sin embargo, en base a la evidencia disponible actualmente, la cantidad de mucosa queratinizada en relación al desarrollo de la peri implantitis permanece controversial (28,29) .…”
Section: Figunclassified